From Directives to Dialogic Voice: Mapping Upward–Downward Communication and Its Barriers in an Indonesian Automotive Marketing Division - Amin, Fatimah Hidayahni; Mulfi, Muhammad Naufal Putra Audy; Sunusi, Seny Luhriyani; Hanafie, Nurharsya Khaer; Sakkir, Geminastiti (Pascasarjana Universitas Negeri Makassar, 2025)
This study analyzed upward and downward communication between employers and employees at PT Bosowa Berlian Motor Makassar. It focused on the phrases and barriers affecting the effective communication. This study employed qualitative research, gathering data through observations with audio recordings and interviews. The subjects were the employers and employees in PT. Bosowa Berlian Motor who were selected purposively considering their availability in the office. The findings reveal that the phrases in terms of the language functions differ in upward and downward communication. For upward communication typically involved suggestions, performance reports, and problem disclosures, while downward communication contained instructions, feedback, and socialization. Key communication barriers were perceptual, emotional, and language obstacles, which were found to hinder message clarity and efficiency. Enhancing openness and consistency of feedback was suggested as a way to improve organizational communication.